The Acquisition and Learning of EFL in A Non-formal English Education in Indonesia - Dwi Ide Rahayu (Universitas Sembilanbelas November Kolaka, 2020)
The acquisition and learning of English as a Foreign Language differs from that of English as a Second Language. In the EFL setting, it is not sufficient if the teaching and learning processes only depend on formal institution. Because of that, the non-formal education plays an important role to support the processes. This research aims at exploring (1) how Kampung Inggris Kebumen – as one of non-formal educations in Indonesia – was built; (2) what the teaching method used to make the learners in Kampung Inggris Kebumen speak English without any reluctance; and (3) how the learners in Kampung Inggris Kebumen acquire and learn English. This research applies qualitative method i.e. a descriptive case study by means of observation and interviews. The result shows that (1) as one of non-formal institution, Kampung Inggris Kebumen plays a significant important role in the success of English teaching and learning in Kebumen Regency, in terms of their collaboration with MGMP Sekolah; (2) Kampung Inggris Kebumen applies the combination of direct method and audio lingual method which are confirmed supportive in the process of acquiring and learning English as a Foreign Language; (3) The students feel that they can decrease their affective filter since the instructors of Kampung Inggris Kebumen use many fun learning activities, provide rich exposures, and intensive time to apply the English in students’ real life. Keywords : acquisition, learning, EFL, non-formal education